1962
DOI: 10.1002/jctb.5010120301
|View full text |Cite
|
Sign up to set email alerts
|

One‐step catalytic conversion of ethanol to butadiene in the fixed bed. I. Single‐oxide catalysts

Abstract: An exhaustive investigation has been carried out on the one‐step catalytic conversion of ethanol to butadiene in the presence of a large number of single‐oxide catalyst systems. The oxides of aluminium, magnesium, iron (III), zirconium and thorium, prepared by calcining the precipitate obtained on addition of aqueous ammonia or ammonium carbonate to a solution of the appropriate nitrate, had good catalytic activity, the process yield of butadiene from ethanol being 24.0, 27.4, 29.8, 35.5 and 31.1%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

1963
1963
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…Apart from the review of those listed, the published literature on the one-step catalytic conversion is meager. While single, binary and ternary-oxide catalyst systems are all used in this field, such as Al 2 [9,[13][14][15][16][17][18][19] and so on, and the process of ethanol conversion to BD is similar.…”
Section: Introductionmentioning
confidence: 98%
“…Apart from the review of those listed, the published literature on the one-step catalytic conversion is meager. While single, binary and ternary-oxide catalyst systems are all used in this field, such as Al 2 [9,[13][14][15][16][17][18][19] and so on, and the process of ethanol conversion to BD is similar.…”
Section: Introductionmentioning
confidence: 98%
“…Usually, enhancement of 1,3-BD selectivities [13,19] and yields [19,27] could be observed when the WHSV was reduced, suggesting the positive effect of contact times on reaction yields, as one might already expect. However, nonlinear effects of ethanol flow rates on 1,3-BD yields were verified over different single and binary metal oxides (such as MgO, ZrO2, Al2O3-MgO, Al2O3-Fe2O3, Al2O3-Cr2O3 and ZrO2-Fe2O3) [30,31].…”
Section: Introductionmentioning
confidence: 98%
“…Usually, reaction variables are investigated using the "change-one-factor-at-atime" method; that is, one variable is changed while the other experimental conditions are kept constant [2,10,12,13,26,27,[29][30][31]. Based on this method, it has been found that temperature exerts an important nonlinear effect on 1,3-BD yields, as observed with help of different catalysts [13,19,26,30,31]. Similar studies have shown that the weight hourly space velocity (WHSV) also modifies 1,3-BD yields and selectivities [2,13,19,26,27,30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…~70% yield [19]. In general, doped-MgO supported on silica [18,[20][21][22][23][24][25][26][27][28][29]] (Lebedev's catalyst) or mixed (supported) oxides [16,19,[30][31][32][33][34][35][36] were used. Various transition metal dopants (Zn, Cu, and Ag) were used to improve MgO/SiO 2 catalyst performance, as well as different synthesis methods and composition of MgO/SiO 2 were investigated, such as Kvisle's wet kneading method [26] and the utilization of clay and sepiolite as the support [21,28].…”
Section: Introductionmentioning
confidence: 99%